IMPLEMENTASI MODEL PBL BERBANTU MEDIA MONOPOLI INTERAKTIF UNTUK MENINGKATKAN HASIL BELAJAR IPAS MATERI KEBUTUHAN DAN KEINGINAN PADA SISWA KELAS V SDN PANYINGKIRAN I - Indira Aliya Rosmaida; Liyra Aulia Azzahra; Evie Fatimah Az Zahra; Pila Delpia Br. Kesogihen; Nurie Yanti Permatasari; Rana Gustian Nugraha (STKIP Subang, 2025)
The use of conventional learning methods that are uninteresting and suboptimal in developing students' critical thinking skills has an impact on low student learning outcomes. This study aims to improve learning outcomes in IPAS material on needs and wants through the implementation of a Problem-Based Learning (PBL) model assisted by interactive monopoly media. This study used the Classroom Action Research (CAR) method with a Kemmis and Mc Taggart design consisting of two cycles, each cycle covering the stages of planning, implementation, observation, and reflection. The research subjects were 25 fifth-grade students. The collected data were analyzed using descriptive qualitative and quantitative approaches, including calculating the average score and the percentage of students who achieved or exceeded the Minimum Mastery Criteria (KKM) compared to the total number of students in the class. The results showed a significant increase between the pre-cycle and cycle II, with the percentage of students who achieved or exceeded the Minimum Passing Criteria (KKM) compared to the total number of students in the class increasing from 65% to 85% and the average score increasing from 72% to 90%. The combination of the PBL model with the use of interactive monopoly media succeeded in transforming difficult economic concepts into an interesting and relevant learning experience, as well as developing critical and collaborative thinking skills, achieving the success criteria of 80% of the number of students who achieved or exceeded the Minimum Passing Criteria (KKM) compared to the total number of students in the class and a minimum average score of 80.